(untitled) (Praxis Educativa, 2022)
This study is an exploratory review about teaching practices at Argentinean public universities published between 2010 and 2019. The sample was constituted by 20 papers. The methodology was qualitative based on content analysis in three axes: work methodology, teaching practices description and characterization of the public university. The results showed a predominance of qualitative methodology, in particular of narrative approach. The aim of studies was teaching practices themselves in most of the papers, followed by directly related issues and, finally, in a few papers teaching practices were part of the aim of the study. Almost all of the papers collected data on public universities, but only a small number included the analysis of the university context in their studies. The results are discussed based on the particularities of university education in the local context.